KERAGAMAN GENETIK 22 AKSESI PADI LOKAL TORAJA UTARA BERBASIS MARKA SIMPLE SEQUENCE REPEATS (SSR) - Ladjao, Holy Ekklesia; Sjahril, Rinaldi; Riadi, Muh. (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2018)
Genetic Diversity of 22 Local Rice Accessions from North Toraja Based on Simple Sequence Repeats (SSR) MarkersABSTRACTOne way to explore the potential of local rice is by the characterization that could obtain genetic diversity of that plants. The aim of this study was to obtain the genetic diversity of 22 local rice accession from North Toraja. Twenty-two of local rice accessions from North Toraja were characterized by 30 SSR markers and using NTSYS pc 2.1 program to analyze genetic diversity. The results showed that twenty-six SSR markers that had been analyzed produced some alelles with a size between 106.75-311 bp, the average number of alleles were 3 and the polymorphism rate was 0.53. On coefficient genetic similarity at 0.38, the population formed three clusters. Cluster I and II were dominated by rice that had no hair on the tip of the grain and cluster III were dominated by rice that had hair on the tip of the grain. There were 105 opportunities to crossing between accessions when the genetic distance was above 0.7.Keywords: genetic diversity, local rice, North Toraja, polymorphism rate, SSR markers ABSTRAKSalah satu cara untuk menggali potensi padi lokal adalah dengan karakterisasi. Dengan adanya kegiatan karakterisasi tersebut maka dapat diketahui bagaimana keragaman genetik dari suatu tanaman. Penelitian ini bertujuan untuk mengetahui keragaman genetik dari 22 aksesi padi lokal Toraja Utara. Duapuluh dua aksesi padi lokal Toraja Utara dikarakterisasi menggunakan 30 marka SSR dan dianalisis keragaman genetiknya menggunakan program NTSYS pc 2.1. Hasil penelitian menunjukkan bahwa duapuluh enam marka SSR yang dianalisis memiliki kisaran ukuran alel antara 106.75-311 bp, dengan jumlah alel rata-rata 3 dan tingkat polimorfisme sebesar 0,53. Koefisien kemiripan genetik 0,38 dan terbentuk 3 klaster. Pada klaster I dan klaster II didominasi oleh padi yang tidak memiliki rambut pada ujung gabahnya, dan pada klaster III didominasi oleh padi yang memiliki rambut pada ujung gabahnya. Selain itu, pada jarak genetik diatas 0,7 terdapat 105 peluang persilangan.Kata Kunci: keragaman genetik, marka SSR, padi lokal, tingkat polimorfisme, Toraja Utara